The Mark Goodson Collection : Modern Masters from the Collection of Mark Goodson. - Glimcher, Arne (New York : PaceWildenstein, 1995)
Arp, Hans (Jean) ; Avery, Milton ; Bacon, Francis ; Beckmann, Max ; Dubuffet, Jean ; Feininger, Lyonel ; Giacometti, Alberto ; Kandinsky, Wassily ; Laurens, Henri ; Leger, Fernand ; Magritte, René ; Miro, Joan ; Noguchi, Isamu ; Picasso, Pablo
biog., tent., bibliog. per kunstenaar
Engels
The Mark Goodson Collection : Modern Masters from The Collection of Mark Goodson, Pace Wildenstei, New York, October 27 - November 25, 1995
boek